Bamboo as an alternative for future wood - Razak Wahab (2015)
Bamboos are considered as an alternative to future wood. Being a fast growing species, bamboo culms needs between 3 - 5 years to mature before they can be turn into various products. Bamboo possesses one of the highest strength properties among woody materials. However, bamboo is susceptible to fungal and insect attack. The properties of bamboo will deteriorate rapidly if the materials are not treated with preservatives. The used of preservative in bamboo has long been recognized as necessary and important if they are to be considered for utilization in furniture and construction industry. This paper discuss the on the properties, potential uses of bamboo with high value-added and some of the constrints faces by the local bamboo industry. Recommendations are also put forwards for the future development of bamboo in Malaysia.